The collection of experiential prescription of traditional korean medicine and secret treatment of heirloom - Hee-Soo Park (Korean Pharmacopuncture Institute, 2004)
Background & Objective : Through the long-term clinical examination experience, interesting informations have been found and passed on to future scholars, enabling research and development without going through the same lengthy procedure, hoarding these precious information to be discovered and preserved as a contribution to Oriental Medical Science. Methods : Personal interviews with seventy-years-old practicing oriental medicine doctors and herbalists with more than 30 years of practice in Gangwon-do, Chungcheongbuk-do, Chungcheongnam-do, and Daejeon area from September to December 2002